Социодраматическая концепция социализации личности - Ехало, В. (Социология: теория, методы, маркетинг, 1999)
The socio-dramatic approach to the problem of socialisation is considered as one oftrends within interactionism. However the eclecticism of theoretical foundations, inherent to socio-drama, understanding of man’s essence as an aggregate of roles setfrom outside, abstracting from integral personalitie’s characteristics and self-consciousness are the main factors inhibiting an adequate scientific description and explanation of social reality. Without wider social context it is impossible to understand interpersonal role relations as preconditions of socialisation. So far as without dramaturgic perspective (in socio-drama terms ) any general picture of social reality will be incomplete, a basic problem is to determine the limits of analogy between theatrical performance and social life, between the clown’s playing and the social actor’s behaviour.